تقييم تركيز بعض العناصر الثقيلة (الكادميوم والرصاص والمنجنيز) بتربة منطقة الحنيوة سرت -ليبيا 150 (Journal of Humanitarian and Applied Sciences, 2023)
This study was conducted in the Haniwa area of Sirte to find out the soil content of some heavy elements (cadmium, lead and manganese)where three sites were identified to collect samples and collected samples in each site of three depths (ground surface – depth 10 cm – depth 20 cm), the content of cadmium, lead and manganese in the agricultural soil samples from the Haniwa area, The results showed that the concentration of elements in all locations was within the permissible limits while the surface samples were higher concentration than those deeper (10 cm, 20 cm) due to the internal movement of the elements, and their higher concentration in the surface due to pollution from traffic, however, these concentrations were within the permissible limits of natural soil.the results also showed that the first and second sites had values close to the concentrations of these elements because they were located at the same distance from the coastal road, and the third site had lower values than them and that of 1500 m from the paved road.
Keywords: heavy metals; topsoil-depth; nostalgia; pollution; manganese; lead-cadmium